A Survey on Artificial Intelligence and Blockchain Clustering for Enhanced Security in 6G Wireless Networks - Shah, A. F. M. Shahen; Karabulut, Muhammet Ali; Kamruzzaman, Abu; Alharthi, Dalal; Bradford, Phillip G. (TECH SCIENCE PRESS, 2025)
The advent of 6G wireless technology, which offers previously unattainable data rates, very low latency, and compatibility with a wide range of communication devices, promises to transform the networking environment completely. The 6G wireless proposals aim to expand wireless communication's capabilities well beyond current levels. This technology is expected to revolutionize how we communicate, connect, and use the power of the digital world. However, maintaining secure and efficient data management becomes crucial as 6G networks grow in size and complexity. This study investigates blockchain clustering and artificial intelligence (AI) approaches to ensure a reliable and trustworthy communication in 6G. First, the mechanisms and protocols of blockchain clustering that provide a trusted and effective communication infrastructure for 6G networks are presented. Then, AI techniques for network security in 6G are studied. The integration of AI and blockchain to ensure energy efficiency in 6G networks is addressed. Next, this paper presents how the 6G's speed and bandwidth enables AI and the easy management of virtualized systems. Using terahertz connections is sufficient to have virtualized systems move compute environments as well as data. For instance, a computing environment can follow potential security violations while leveraging AI. Such virtual machines can store their findings in blockchains. In 6G scenarios, case studies and real-world applications of AI-powered secure blockchain clustering are given. Moreover, challenges and promising future research opportunities are highlighted. These challenges and opportunities provide insights from the most recent developments and point to areas where AI and blockchain further ensure security and efficiency in 6G networks.
Keywords: AI; blockchain; clustering; energy efficiency; security; challenges; future perspectives; 6G; COMMUNICATION; PRIVACY; VISION; Computer Science; Materials Science